2023
DOI: 10.18287/jbpe23.09.010305
|View full text |Cite
|
Sign up to set email alerts
|

Features of L-Menthol Crystallization in Optically Active Medium Based on L- and D-Asparaginate Chitosan

Abstract: The phase separation kinetics of an ethanolic L-menthol solution in an aqueous solution of optically and biologically active chitosan L-and D-aspartate was studied. It has been established that this process proceeds according to the extraction crystallization mechanism and combines two types of phase separation, namely: liquid-liquid and liquid-crystal. The effect of aspartic acid stereoisomer, chitosan molecular weight, and polymer: acid ratio on the optical, structural-morphological, and dimensional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…20 They suggested that the system under study L-menthol can be used for encapsulation of hydrophobic drugs, fabrication of chiro optic waveguides, and sensors for biomedical purposes as well as studying fundamentals of phase separation for biosystem, also include the development of new pharmaceutical drugs for the treatment of depression and rare incurable diseases. 21 In skin permeation, L-menthol and some concentration of alcohol can enhance the effectiveness of morphine hydrochloride (MPH), confirmed by a thermodynamically active system. 22 In L-menthol, whisker growth and high volatility are important problems for storage and its application process.…”
Section: Introductionmentioning
confidence: 99%
“…20 They suggested that the system under study L-menthol can be used for encapsulation of hydrophobic drugs, fabrication of chiro optic waveguides, and sensors for biomedical purposes as well as studying fundamentals of phase separation for biosystem, also include the development of new pharmaceutical drugs for the treatment of depression and rare incurable diseases. 21 In skin permeation, L-menthol and some concentration of alcohol can enhance the effectiveness of morphine hydrochloride (MPH), confirmed by a thermodynamically active system. 22 In L-menthol, whisker growth and high volatility are important problems for storage and its application process.…”
Section: Introductionmentioning
confidence: 99%